2021
DOI: 10.1007/s42452-020-04091-1
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties of highly porous silver oxide thin film

Abstract: In this paper, we report oxidation time effect on highly porous silver oxide nanowires thin films fabricated using ultrasonic spray pyrolysis and oxygen plasma etching method. The NW’s morphological, electrical, and optical properties were investigated under different plasma etching periods and the number of deposition cycles. The increase of plasma etching and oxidation time increases the surface roughness of the Ag NWs until it fused to form a porous thin film of silver oxide. AgNWs based thin films were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 56 publications
(66 reference statements)
3
25
0
Order By: Relevance
“…Al-Sarraj et al indicated the X-ray diffraction peaks of a silver-oxide film at 2θ = 32.3º and 37.3º, corresponding to Ag2O (111) and Ag2O (200). The AgO was at 2θ = 34.1º and the mixed-phase Ag/Ag2O formation was 2θ = 39.6º [44]. In our study, no significant intensities of AgO and Ag2O peaks shown in Figure 5(a) might indicate the high purity silver structure of the stored samples, as studied by Waterhouse et al [45].…”
Section: Xrd Of Agnp Structuressupporting
confidence: 47%
“…Al-Sarraj et al indicated the X-ray diffraction peaks of a silver-oxide film at 2θ = 32.3º and 37.3º, corresponding to Ag2O (111) and Ag2O (200). The AgO was at 2θ = 34.1º and the mixed-phase Ag/Ag2O formation was 2θ = 39.6º [44]. In our study, no significant intensities of AgO and Ag2O peaks shown in Figure 5(a) might indicate the high purity silver structure of the stored samples, as studied by Waterhouse et al [45].…”
Section: Xrd Of Agnp Structuressupporting
confidence: 47%
“…The XPS spectrum of Ag 3d was separated into two peaks at 367.8 and 373.8 eV corresponding to Ag 3d 5/2 and Ag 3d 3/2 , which were deconvoluted to AgO (367.8 and 373.8 eV) and AgO x (367.5 and 373.5 eV), respectively. [ 75,76 ] Note that the FWHM values of Ag 3d are determined to be 1.02 eV for AgO and 1.32 eV for AgO x . [ 77 ] The Au 4f XPS survey spectra exhibited two significant peaks at ≈83.5 and ≈87.4 eV corresponding to the Au 4f 7/2 and 4f 5/2 characteristic signals and 1.14 eV for FWHM value of Au peak, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 532.38 eV may have been because of the presence of superoxide, leading to increased toxicity or, as per some studies, may reflect the presence of contamination [ 35 ], which in our case could have been an outcome of biological synthesis. The Ag 3d binding energy values observed in the sample were 374.08 eV and 366.1 eV corresponding to Ag and Ag (III) [ 36 ]. These observations confirmed the presence of mainly AgNPs and a small amount of Ag 4 O 4 (silver (I, III)) in this sample.…”
Section: Resultsmentioning
confidence: 99%